Early predictors of impaired sleep: a study on life course socioeconomic conditions and sleeping problems in older adults. (1st February 2020) - van de Straat, Vera; Cheval, Boris; Schmidt, Ralph E.; Sieber, Stefan; Courvoisier, Delphine; Kliegel, Matthias; Burton-Jeangros, Claudine; Cullati, Stéphane; Bracke, Piet
Abstract: Objectives: This study aimed to assess how childhood socioeconomic conditions are associated with sleeping problems in older adults and how this association may be mediated by socioeconomic conditions across the lives of individuals using a life course perspective. Since the life course opportunities differ systematically between men and women, attention was given to gender differences in the association. Methods: Data from 23, 766 individuals aged over 50 years of the longitudinal Survey of Health, Ageing and Retirement in Europe (SHARE) were used. Logistic mixed-effect models were estimated to examine the associations between childhood socioeconomic conditions and the presence of sleeping problems. Results: For women, the analyses showed an association between childhood socioeconomic conditions and sleeping problems. For men, only current socioeconomic conditions were found to be relevant for sleep. The importance of childhood socioeconomic conditions for sleeping problems did not affect the evolution of sleeping problems over ageing. Conclusion: In this study no empirical support was found for processes of cumulative advantage/disadvantage or age-as-leveler. However, childhood does seem to be a critical period for the sleep of women, because the association with childhood socioeconomic conditions remains even when the circumstances later in life are considered. These findings, in particular the gender differences in the association, underline the importance of tracking life course patterns in the study of sleeping problems in older adults.